Partnering to Build a Pantry: A University Campus Responds to Student Food Insecurity. Issue 3 (2nd July 2016) - Twill, Sarah E.; Bergdahl, Jacqueline; Fensler, Rebecca
ABSTRACT: The current economic climate negatively affects college students' ability to pay higher education costs. Rising costs, including tuition and living expenses, coupled with the decreased buying power of federal aid, may create financial difficulty for students. One consequence may be food insecurity. This article details the cross-campus partnership efforts of one university to establish a campus food pantry to serve students. The process of establishing a pantry including assessing food insecurity on campus, fund-raising, creating pantry policies, and recruiting and training volunteers are discussed. Lessons learned about pantry usage, and ways to improve operations are also presented.